다발성 장기 경색을 동반한 폐선암 1례 - 박창환; Chang Whan Park; 이정훈; Chung Hoon Lee; 황준화; Jun Wha Whang; 장일권; Il Gwon Jang; 박형관; Hyeong Kwan Park; 김영철; Young Chul Kim; et al. (Tuberculosis and respiratory diseases, 1997)
The relationship between neoplastic disease and thromboembolic disorders has been recognized since 1865, when Armand Trousseau first reported a high incidence of venous thrombosis in a series of patients with gastric carcinoma. The overall incidence of thromboembolic disease in patients with cancer has been reported to vary 1% to 15%. In a prospective study, Ambrus and associates reported that thrombosis and/or bleeding was the second most common cause of death in haspitalized cancer patients. We report a case who presented as a thromboembolic disease and subsequently confirmed to have an underlying lung malignancy. This 45 years old male patient visited our hospital with abdominal pain and distention of 3 days duration. Abdominal CT scan revealed multiple splenic and renal infarctions. On 20th haspital day, drowsy mental status was developed and hemorrhagic cerebral infarction was noted in brain CT scan. Chest CT scan revealed a 4cm sized spiculated mass on left lung apex and multiple paratracheal lymph adenopathy. With surgical biopsy of left supraclavicular lymph nodes, this patient was confirmed to have adenocarcinoma. 저자들은 임상적으로 신장, 비장 그리고 뇌에 다발성 및 재발성 경색이 발생하여 주요 원인 질환으로 폐선암을 진단하였던 1예를 경험하였기에 문헌 고찰과 함께 이에 보고한다. 다발생 경색의 원인기전으로는 비세균성 혈전성 심내막염 또는 파종성 혈관내 응고증에 의한 in situ thrombosis 등이 추정되었다.